2015
DOI: 10.1080/14036096.2015.1031275
|View full text |Cite
|
Sign up to set email alerts
|

Feeling at Home in a Multigenerational Household: The Importance of Control

Abstract: The importance of property ownership for feelings of control and ontological security has received significant academic attention. Yet tenure may not be the only indicator of control over one's dwelling. This paper considers the importance of control within the household in relation to household members' feelings of home and highlights the importance of one's relationship with other household members and their relative control over decisionmaking and the use of space. It draws upon research on multigenerationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…Importantly, 'healthy housing' goes beyond just a physical shelteras the World Health Organisation argues: 'to have a home, a place which protects privacy, contributes to physical and psychological wellbeing and supports the development and social integration of its inhabitants' (Bonnefoy, 2007, p. 413). Housing and home are therefore linked to health and wellbeing through the importance of physical shelter as well as elements such as agency and control, all of which contribute to ontological security (Easthope et al, 2015;Giddens, 1991). However, housing and its relationship to health and well-being is less explored for people with refugee and asylum seeker backgrounds, and only a small amount of this research has been conducted in resettlement countries (see Ziersch & Due, 2018 for review of this literature).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, 'healthy housing' goes beyond just a physical shelteras the World Health Organisation argues: 'to have a home, a place which protects privacy, contributes to physical and psychological wellbeing and supports the development and social integration of its inhabitants' (Bonnefoy, 2007, p. 413). Housing and home are therefore linked to health and wellbeing through the importance of physical shelter as well as elements such as agency and control, all of which contribute to ontological security (Easthope et al, 2015;Giddens, 1991). However, housing and its relationship to health and well-being is less explored for people with refugee and asylum seeker backgrounds, and only a small amount of this research has been conducted in resettlement countries (see Ziersch & Due, 2018 for review of this literature).…”
Section: Introductionmentioning
confidence: 99%
“…There are disadvantages though as prolonged caregiving for elders may lead to prolonged conflict or intergenerational conflicts related to caregiving. Easthope et al (2015) focused their research on the conflicts that arise within co-residence and how owning a home may provide people with a different sense of security than renting does. Multigenerational families may consist of multiple adults who negotiate their actions within the household, and legal ties to the home are important in giving people a sense of authority and control over their environment.…”
Section: Potential Conflict In Multigenerational Familiesmentioning
confidence: 99%
“…This can lead to lower levels of self-efficacy. Easthope et al (2015) suggest joint home ownership among adults in multigenerational families would be especially important in mitigating some of these issues.…”
Section: Potential Conflict In Multigenerational Familiesmentioning
confidence: 99%
“…Significantly, however, research evidence has shown that post the global financial crisis of 2008, MGH living has become increasingly prevalent in countries which previously had favoured single or two generational modes of occupancy (Generations United, 2017;Li and Shin, 2013;. Liu and Easthope, 2012;Easthope et al, 2015). For example, studies have shown how following the credit crunch era, people in the Czech Republic and the Netherlands have turned to intergenerational living as a means of counteracting adverse economic circumstances and societal shifts (Kneale et al, 2012).…”
Section: Emergence Of Multi Generational Living In England -mentioning
confidence: 99%